Warfarin Pharmacogenetics: Does More Accurate Dosing Benefit Patients? - Eby, Charles (Seminars in Thrombosis and Hemostasis, 2012)
After a decade of clinical investigation, pharmacogenetic-guided initial dosing of warfarin is at a crossroads. Genotypes for two single nucleotide polymorphisms (SNPs) in the cytochrome P 450 2C9 gene, affecting warfarin metabolism, and one SNP in vitamin K reductase complex 1 gene, affecting warfarin sensitivity, account for approximately 30% of therapeutic warfarin dosing variability in whites and Asians. Incorporating this genetic information, along with patient's age, body size, and other clinical information improves the accuracy of initial warfarin dosing. Currently, there is insufficient evidence to support the clinical benefits and cost effectiveness of routine warfarin pharmacogenetics. Results from ongoing international randomized clinical trials should provide clarity about the place of warfarin pharmacogenetics in personalized medicine.
Keywords: warfarin; oral anticoagulant therapy; vitamin K antagonist; pharmacogenetics